The Gebelein Region in the Third Intermediate and Late Periods - Ejsmond, Wojciech; Kaczanowicz, Marta (Études et Travaux, 2024)
While relatively much is known of Gebelein in the second and third millennia BCE, as well as the Ptolemaic times, the role of the town of Per-Hathor and its surrounding in the Third Intermediate (c. 1076–747 BCE) and Late (c. 747–332 BCE) periods remains largely obscure. The aim of this paper is to examine the existing sources pertaining to the history of Gebelein with the particular focus on state activities in the area, diachronic changes in settlement pattern and sacral topography, as well as funerary landscape in the first three-quarters of first millennium BCE and analyse the available information in a regional context. For this, published and unpublished records are utilised, together with the results of the current field prospection in Gebelein.